THE ROLE OF ISLAMIC RELIGIOUS EDUCATION LEARNING EVALUATION (STUDY AT SMP 2 COLOMADU KARANGANYAR CITY) - Rochandhito, Hidayah; Inayati, Nurul Latifatul (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2023)
The purpose of the study was to determine the assessment of PAI learning in SMP 2 Colomadu Karanganyar technical evaluation conducted at SMP 2 Colomadu Karanganyar technical evaluation conducted at SMP 2 Colomadu Karanganyar This type of research is a qualitative descriptive study, data collection techniques using observation, interviews, and documentation techniques. Data analysis techniques use inductive and deductive frameworks. The results of the study, namely the implementation of the evaluation is taken from the results of daily tests, midterm exams and final exams evaluation management includes planning, managing the implementation of organization and evaluation. Technical Evaluation of PAI Learning leads to the cognitive domain, affective domain and psychomotor domain. evaluation of PAI Learning techniques applied in SMP 2 Colomadu Karang anyar non-test techniques SMP 2 Colomadu Karang anyar This type of research is a qualitative descriptive study, data collection techniques using observation, interviews, and documentation techniques. Data analysis techniques using inductive and deductive frameworks. The results of the study, namely the implementation of the evaluation is taken from the results of daily tests, midterm exams and final exams of the semester evaluation management includes planning, management of organizational implementation and evaluation. Technical evaluation of PAI learning leads to the cognitive domain, affective domain and psychomotor domain.